Profile of the Patients Serviced in a High Complexity System - Mondelli, Maria Fernanda Capoani Garcia; Silva, Letícia de Sousa Lobo (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Hearing loss (HL) may cause severe consequences for the development of speech and learning. A resource of rehabilitation of the hearing impaired is the hearing aid (AASI). Information actions to the population and health professionals and approval of a law that assures the hearing impaired access to early diagnosis and intervention follow-up are seen as necessary measures. Such aspects have been contemplated by the Health Ministry (MS) in the publication of Administrative Rules GM no. 2.073, of September 28, 2004, and 587, of October 07, 2004. The Phonoaudiological Clinic of the Phonoaudiology Course of FOB/USP is certified by Administrative Rule GM/MS no. 2073, of September, 2004.Objective: To draw the profile of the patient serviced in a high complexity system with the goal of using the results found as a starting-point for acquisition of hearing aid, planning of auditory rehabilitation and structuring of follow-up groups for fitted patients.Method: Retrospective study. Reports review of 185 patients regularly registered in the period from August 2003 through August 2009. The data researched included: sex, age, social class, precedence, HL type and degree, HL etiology and type of hearing aid indicated.Results: There was a prevalence of male older low class patents with neurosensorial, bilateral and moderate level hearing loss.Conclusion: Prevalence of moderate level bilateral neurosensorial hearing loss with a higher index of older patients with the use of digital technology at a higher proportion.
Keywords: hearing loss; health systems; ranking